METODA IRFĀNĪ DALAM JEJARING TRANSMISI QIRĀ’ĀT ‘ĀṢIM: Hubungan Guru dan Murid dalam Jalur ‘Āṣim - Nurul Hikmah; Ibadurrahman Habib El Hakiem; Dzawata Afnanan Habib El Hakiem (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines the epistemological and spiritual dimensions embedded in the transmission network of the Qirāʾāt of ʿĀṣim, with a particular focus on the presence of ʿirfānī elements that are rarely articulated explicitly in classical qirāʾāt literature. Although the early sources do not employ the term “ʿirfānī methodology,” the findings demonstrate that the pedagogical practices within the transmission chain—from al-Sulamī to ʿĀṣim, Ḥafṣ, and Syuʿbah—are fundamentally infused with principles of tazkiyah (spiritual purification), adab (ethical discipline), ṣuḥbah (intimate companionship), and intiḳāl al-ḥāl (transmission of spiritual states), which collectively form the essence of the ʿirfānī epistemic tradition. By analyzing primary sources such as Ghāyat al-Nihāyah, al-Nashr, and Jamāl al-Qurrāʾ, alongside contemporary academic studies, this research reveals that the authoritative strength of the ʿĀṣim tradition rests not only upon phonetic accuracy and textual conformity, but also upon the spiritual integrity of its transmitters, who safeguarded the sanad through exemplary character and sustained talaqqī–musyāfahah training. The study concludes that the methodological resilience of the ʿĀṣim reading lies in its integration of technical validity (rasm, phonetics, tawātur) and spiritual validity (presence of heart, sincerity, and ethical comportment). These findings open new perspectives for understanding qirāʾāt as a discipline rooted equally in technical mastery and spiritual formation, offering fresh contributions to contemporary Qur’anic pedagogy and the preservation of authentic sanad traditions.